1995
DOI: 10.1074/jbc.270.25.15029
|View full text |Cite
|
Sign up to set email alerts
|

5-Oxo-eicosanoids Are Potent Eosinophil Chemotactic Factors.

Abstract: Human eosinophils produce upon treatment with 5-oxo-eicosatetraenoic acid or (5S,15S)-dihydroxyeicosatetraenoic acid a potent eosinophil-chemotactic eicosanoid, 5-oxo-15-hydroxy-(6E,8Z,11Z,13E)-eicosatetraenoi c acid (5-oxo-15-HETE). 5-Oxo-15-HETE induces human eosinophil (Eo) chemotaxis at nanomolar concentrations with an efficacy in vitro comparable to that seen for platelet activating factor. Comparison of Eo chemotactic activities of several structurally related eicosanoids with different substituents and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…Another 15-LO-1-derived metabolite, 5-oxo-15-hydroxy-6,8,11,13-eicosatetraenoic acid, produced by eosinophils, has been reported to be a potent chemotactic agent for human eosinophils (21). However, there are also indications that 15-LO-derived metabolites could play an antiinflammatory role because 15-LO-1 can be involved in the formation of lipoxins (22).…”
mentioning
confidence: 97%
“…Another 15-LO-1-derived metabolite, 5-oxo-15-hydroxy-6,8,11,13-eicosatetraenoic acid, produced by eosinophils, has been reported to be a potent chemotactic agent for human eosinophils (21). However, there are also indications that 15-LO-derived metabolites could play an antiinflammatory role because 15-LO-1 can be involved in the formation of lipoxins (22).…”
mentioning
confidence: 97%
“…The boldface letters represent amino acids conserved in all of the prostanoid receptors aligned in Fig 6. The conserved amino acids in the prostanoid receptor are also found in TG1019: 103 5-oxo-ETE exhibited the most potent agonistic activity against TG1019. This eicosanoid is known as a potent chemotactic factor of eosinophils and neutrophils (37)(38)(39)(40). O'Flaherty et al (41,42), and O'Flaherty and Rossi (43) had revealed that the chemotactic activity would be mediated through a pertussis toxin-sensitive GPCR.…”
Section: Fig 5 Effect Of 5-oxo-ete On Forskolin-stimulated Camp Promentioning
confidence: 99%
“…S2D). Six carbon-carbon double bonds hydrogenated 14S,21R-diHDHA (H 12 -14S,21R-diHDHA) was generated by bubbling hydrogen gas through a methanol solution of 14S,21R-diHDHA, in which Adam's catalyst PtO 2 (ϳ1 mg) was suspended (20 min, room temperature) (41)(42)(43).…”
Section: Sample Preparation and Lc-uv-ms/ms Analysis Of Lipid Mediatomentioning
confidence: 99%